Peran Pekerja Sosial dalam Mendampingi PPKS di Dinas Sosial Kota Medan: The Role of Social Workers in Accompanying PPKS in the Medan City Social Service - Saskia Amanda Hasibuan; Husni Thamrin; Bengkel Ginting (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This research aims to explore the role of social workers in assisting individuals with social welfare issues (PPKS) at the Social Services Office of Medan City. Social workers have an important responsibility in providing comprehensive assistance and support to PPKS, which includes individuals and families facing social, economic, and health problems. The research method used is qualitative with a case study approach. Data were obtained through in-depth interviews, participatory observation, and document analysis. The results show that social workers play roles in problem identification, intervention planning, empowerment program implementation, and monitoring and evaluation of intervention outcomes. Additionally, social workers function as liaisons between PPKS and available resources, both from the government and non-governmental organizations. In conclusion, the role of social workers is crucial in ensuring the well-being of PPKS through a holistic and sustainable approach.